Óleos essenciais no manejo da mancha marrom de alternaria em tangerineira "DANCY" - Porcino, Mirelly Miguel (2018)
Brazil is considered the fifth highest producer of tangerines in the world. However, its production has been decreasing due to the attack of diseases, especially the brown spot of alternaria, which has as its causal agent the Alternaria alternata (Fr: Fr) Keissler f. sp. Citri that causes serious economic problems in the culture. In the management of, alternative products are used as the essential oils. This work aimed to determine the effect of different essential oils on A. alternata f. sp. Citri in vitro, in 'Dancy' tangerine (Citrus tangerina Hort. ex Tanaka). The experiments were carried out at the Phytopathology, Biology and Post-Harvest Technology Labs and in a greenhouse at the Centro de Ciências Agrárias, UFPB. Two experiments were carried out: In the first experiment three isolates of A. alternata f. sp. citri (Massaranduba-Paraíba, Pratânia-São Paulo e Trás dos Montes-Portugal) were used. To verify the effect of the treatments on the isolates cultivated in vitro, the essential oils of grape seeds, sunflower, eucalyptus, ginger, copaiba, mint, fennel, citronella, cloves and flax seeds were added at a concentration of 1% diluted in BDA media culture with pH 6.0.In the plates center were putted a 5 mm diameter disk of the fungus colony for the in vitro experiment. The fruits were treated with the same essential oils used in vitro experiment, diluted in sterile distilled water and additional controls composed by Thiabendazole (400 mL / 100L) and ADE (untreated), immersed in the treatments for 5 min. The fruits were sprayed with the spore suspension at the concentration of 105 conidia / mL of A. alternata f. sp. citri. Mycelial growth rate index, colony diameter (for seven days), conidia and conidial size (in vitro) were evaluated; severity of disease in fruits (by scale of specific note) in vivo. The physical-chemical analyzes were composed by total soluble solids, titratable acidity, total soluble solids ratio and titratable acidity, pH, firmness, juice yield, ascorbic acid, totaling five evaluations and loss of mass and, enzymatic activity (peroxidase, polyphenoloxidase and phenylalanine ammonium lyase) in 'Dancy' tangerine fruits. The design was completely randomized with 12 treatments, consisting of four replicates of three plates (in vitro) and four replicates of three fruits (in vivo). According to the results, the essential oils of mint, eucalyptus, fennel and citronella were efficient in the in vitro control of the pathogen, totally inhibiting the fungus colonies growth. Eucalyptus oil was efficient in the management of A. alternata f. sp. citri in 'Dancy' in tangerine fruits compared withother treatments. The essential oils did not interfere on post-harvest quality of 'Dancy' tangerine. The enzymatic activity in fruits increased in the second evaluation period. In the second experiment, two isolates of A. alternata f. sp. Citri (Massaranduba-PB and Pratânia-SP). Tangerine 'Dancy' seedlings were treated with essential oils of ginger, copaiba, mint, fennel and citronella at a concentration of 1% added Tween 80 and ADE, fungicideTiabendazole (400 mL / 100L) and ADE (untreated), sprayed to the point of drainage. For pathogen inoculation, the suspension was adjusted to 105 conidia/mL sprinkled to the point of drainage. The parameters evaluated were disease severity and gas exchange in 'Dancy' mandarin seedlings. Disease severity and gas exchange data were analyzed in a viii completely randomized design, consisting of seven treatments and four replicates of two plants. The results showed that the essential oil of fennel was efficient in the management of A. alternata f. sp. citri in 'Dancy' tangerine seedlings and the essential oils of citronella, copaiba and ginger do not negatively affect the gas exchange on seedlings.